Life Cycle Assessment (LCA) of hazardous waste generated by Crime Scene Laboratories (CSL) in Mpumalanga, South Africa - Maqutu, Vuyo Zandisile Zamo (My University, 2017)
Mismanagement of hazardous waste has been witnessed in many part of the world including South Africa, and it has costed the environment too much pollution. This study aimed to analyse Life Cycle Assessment (LCA) methodology of Crime Scene Laboratory waste. To this aim, aspects analysed included assessment of potential environmental impacts evaluated with each stage of waste management, such as waste generation stage, processing, collection, transportation and disposal. Results showed that crime scene laboratories were only addressing the cost associated with collection and transportation of their waste for disposal, and no assessment of environmental impacts by means of LCA was practiced. This study also investigated how hazardous waste generation is managed. Data was collected from six laboratories (Witbank, Secunda, Ermelo, Nelspruit, Acornhoek and Lydenburg) for the period of eight months. Aspects analysed included suitability of temporary waste storage which should be able to prevent release of waste, use of waste registers which are used to determine how much time is taken for waste to be disposed, regular inspection of waste bins for monitoring of leakages and overfilling, and the competency of people managing waste. Findings showed that CSL’s have poor waste storage facilities and waste is temporary stored inside the laboratories and building passages when the space inside the laboratories is a challenge due to delayed waste collection by contracted service provider. Results also showed that no waste minimisation strategies were established to reuse generated waste for secondary products to reduce quantity aimed for disposal. Furthermore, production of waste per site, nature of waste, months, and waste type was compared, and Statsoft statistics analysis technique for this purpose was used to analyse these differences which summarized variation across the sites. The level of variation was estimated at significant level of 0.05.Results showed that Ermelo produced significantly more non-anatomic biological waste, Witbank produced significantly more heavy metals and Lydenburg more Inorganic and organic acids and bases different to other locations. Non-anatomic biological waste was significantly produced more in January, May, June and August different to other months. Statistics results on the nature of waste showed that chemical, biological and miscellaneous waste was significantly produced more in February and May different to other months. Non –chlorinated waste was significantly produced more in January. Statistics results on waste types showed that all types of waste were significantly produced more in February different to other months, also in March all waste types were significantly produced, except non-anatomic biological waste, which was significantly produced more in April, July and August. The study makes recommendations on adoption of LCA, waste separation methods, storage and minimisation methods and training of waste handlers as an important aspect of environmental protection. The study also recommends an adoption of the Environmental Management system, ISO 14000 by the CSL’s. The standard according to the literature encourages and gives guidance in achieving cleaner productions including waste separations and minimisations in order to avoid pollution of natural resources by mismanagement wastes.
A research report submitted in partial fulfilment of the requirements for the Degree of Masters of Environmental Sciences by coursework and research report to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2017.
Keywords: Crime laboratories; Chemicals--Safety measures; Chemical engineering--Safety measures